Postoperative and midterm outcomes of minimally invasive and endoscopic great saphenous vein harvesting for coronary artery bypass grafting - a prospective analysis - Simek, M; Nemec, P; Bruk, V; Gwozdziewicz, M; Fluger, I; Langova, K (The Thoracic and cardiovascular surgeon, 2007)
BACKGROUND: We sought to determine whether the postoperative and midterm outcomes of minimally invasive and endoscopic great saphenous vein harvesting are comparable. METHODS: From February 2004 to September 2006, 120 patients underwent minimally invasive vein harvesting, and subsequently 150 patients had endoscopic vein harvesting for CABG. Patients were evaluated prospectively for wound-healing disturbances, residual leg oedema, pain intensity and saphenous neuropathy on the 7th postoperative day and after 3 months. RESULTS: Both harvesting techniques were associated with a low incidence of wound-healing disturbances; nevertheless, minimally invasive vein harvesting was associated with a significantly higher incidence of residual oedema (28 % vs. 13 %; P < 0.05), (19 % vs. 6 %; P < 0.001), pain (20 % vs. 9 %; P < 0.05), (10 % vs. 6 %; P < 0.05), and saphenous neuropathy (23 % vs. 7 %; P < 0.001) (14 % vs. 3 %; P < 0.001) during follow-up on the 7th postoperative day as well as 3 months after surgery, respectively. Mean harvesting time (40.6 +/- 15.5 vs. 43.9 +/- 10.2 min; P = 0.09), conversion rate (3 % vs. 2 %; P = 0.71), and injury per conduit (0.3 +/- 0.2 vs. 0.3 +/- 0.1; P = 0.91) were comparable for both groups. CONCLUSIONS: Endoscopic vein harvesting seems to be superior to minimally invasive vein harvesting in terms of a significant reduction of residual leg oedema, pain intensity and particularly saphenous neuropathy in the postoperative and midterm follow-up.
Keywords: výsledek terapie; Minimally Invasive Surgical Procedures; spokojenost pacientů; koronární bypass; Male; odběr tkání a orgánů; Middle Aged; Coronary Artery Disease; pooperační bolest; Endoscopes; Equipment Design; následné studie; Coronary Artery Bypass; měření bolesti; Aged; Prospective Studies; mužské pohlaví; senioři; Patient Satisfaction; incidence; Peripheral Nervous System Diseases; design vybavení; nemoci koronárních tepen; Follow-Up Studies; Treatment Outcome; Time Factors; Edema; Endoscopy; Tissue and Organ Harvesting; lidé; Wound Healing; ženské pohlaví; Humans; časové faktory; nemoci periferního nervového systému; Saphenous Vein; hojení ran; endoskopie; miniinvazivní chirurgické výkony; Pain, Postoperative; vena saphena; Female; Pain Measurement; lidé středního věku; Incidence; endoskopy; edém; prospektivní studie